2021- CSA Monitoring: Hoima Climate-Smart Village (Uganda) - Bonilla-Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Recha, John W.M.; Ambaw, Gebermedihin; Kakeeto, Ronald (2022)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Hoima Climate Smart Village (Uganda) in October 2021.